Special Settlement Development Program for Suku Anak Dalam (SAD): Merangin Regency (in press) - Auzafani, Fadhillah; Purnaweni, Hartuti; Priyadi, Budi Puspo (Publik : (Jurnal Ilmu Administrasi), 2024)
The Resettlement of Alienated Communities (PKMT) program, in the aspect of social development carried out by the government. This research focuses on the effectiveness of the SAD settlement development program through the PKSTM program. The formulation of the problem How is the effectiveness of the special housing construction program for SAD through the Program for the Welfare of Alienated Communities (PKSMT). The purpose of this research is to analyze the effectiveness of the special house construction program for SAD through the Development of the Welfare of Alienated Communities (PKSMT) program. The urgency of the research is as a forum for the development of government programs for disadvantaged communities, especially SAD, through this program can provide welfare and openness of SAD to the outside world. The method used in this research is field research with a qualitative descriptive approach, with the type of data used primary data and secondary data. Data sources were obtained from the Social Service, mass media, journal articles and documentation. Data collection was carried out using the interview method. This research was conducted. The results of the analysis show that the SAD settlement building program has not been effective, because: the construction of special SAD settlements is not evenly distributed throughout the SAD community, the government's efforts are not optimal in running the PKSMT program and psychologically it takes a long time to change the patterns and habits of life of the SAD community from living in melangun (moving) to living in a settled area.